Statue of Buddha (Bhayamudra), at the Haw Phra Kaew Museum (Vientiane) - Pierre André Leclercq (Wikimedia Commons, 2014)
Notice iconographique issue de Wikimedia Commons. Titre: Statue of Buddha (Bhayamudra), at the Haw Phra Kaew Museum (Vientiane). Statue of Buddha Dispelling Fear (Bhayamudra), Haw Phra Kaew, Vientiane. Laos
Licence Creative Commons Attribution-Share Alike 4.0 via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons